An HCV‐positive recipient of an HCV‐positive donor liver successfully treated before and immediately after liver transplant with daclatasvir, sofosbuvir, and ribavirin. Issue 4 (3rd February 2017) - Poordad, Fred; Lawitz, Eric; Gutierrez, Julio A.; Guerrero, Juan; Speeg, Kermit; Swenson, Eugene S.
Key Clinical Message: This case suggests that initiation of HCV therapy immediately after liver transplantation with well‐tolerated, all‐oral regimens may achieve a virologic cure in HCV‐positive recipients, thus preventing post‐transplant HCV recurrence and associated disease progression. This strategy may broaden utilization of HCV‐positive donor livers, potentially including HCV‐negative transplant recipients. Abstract : This case suggests that initiation of HCV therapy immediately after liver transplantation with well‐tolerated, all‐oral regimens may achieve a virologic cure in HCV‐positive recipients, thus preventing post‐transplant HCV recurrence and associated disease progression. This strategy may broaden utilization of HCV‐positive donor livers, potentially including HCV‐negative transplant recipients.